1989
DOI: 10.1111/j.1752-1688.1989.tb03104.x
|View full text |Cite
|
Sign up to set email alerts
|

MUNICIPAL UTILIZATION OF WATER DEMAND MANAGEMENT: THE ONTARIO EXPERIENCE1

Abstract: Managing the demand for municipal water supply has become a viable alternative or supplement to traditional supply management responses. Though senior governments in Canada are committed to the concept, there is a lack of knowledge concerning the level of use of the demand management concept and little promotion of water conservation. This paper assesses the extent of the use of this concept as it applies to municipal water supply across southern Ontario and examines factors that influence the variation in use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…They asked municipalities if they had introduced new "laws/bylaws/regulations/ordinances" as part of their demand side management initiative; 55% of responding communities in their study indicated that they had. Kreutzwiser and Feagan's (1989) 1987 survey apparently is the only previous effort to capture the ordinance experiences of a large proportion of Ontario municipalities.…”
Section: Municipal Ordinances That Promote Water Conservation and Effmentioning
confidence: 99%
See 2 more Smart Citations
“…They asked municipalities if they had introduced new "laws/bylaws/regulations/ordinances" as part of their demand side management initiative; 55% of responding communities in their study indicated that they had. Kreutzwiser and Feagan's (1989) 1987 survey apparently is the only previous effort to capture the ordinance experiences of a large proportion of Ontario municipalities.…”
Section: Municipal Ordinances That Promote Water Conservation and Effmentioning
confidence: 99%
“…To supplement findings from the above, data also were gathered regarding the overall effectiveness of demand side measures, and factors that facilitated and constrained their use. All types of municipalities were represented in the survey, ranging from dispersed rural townships to cities and regional munici- palities. In addition to presenting a comprehensive, up-todate overview of municipal demand side practices in Canada's largest province, the paper highlights areas where progress has been made since the last major assessment of water conservation practices in Ontario (Kreutzwiser and Feagan, 1989). Where appropriate, comparisons also are made with other studies that address demand side management in Ontario, including Schaefer and Hurst's (1997) analysis of the application of metering and water rate structures among Ontario municipalities over the 1983-1994 period, Wailer and Scott's (1998) national overview of municipal water demand side measures, and Environment Canada's regular surveys of water rates (e.g., Tate, 1989;Lacelle, 1992, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kreutzwiser and Feagan (1989) found that 35% of 219 Ontario municipalities surveyed in 1987 had ordinances restricting outside use, compared with almost 60% of 153 Ontario municipalities surveyed in 1998 (de Loë et al, 2001). Kreutzwiser and Feagan (1989) found that 35% of 219 Ontario municipalities surveyed in 1987 had ordinances restricting outside use, compared with almost 60% of 153 Ontario municipalities surveyed in 1998 (de Loë et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Restrictions on outdoor water use have become more common. Kreutzwiser and Feagan (1989) found that 35% of 219 Ontario municipalities surveyed in 1987 had ordinances restricting outside use, compared with almost 60% of 153 Ontario municipalities surveyed in 1998 (de Loë et al, 2001). Outdoor water use ordinances are sometimes linked to drought contingency plans.…”
Section: Introductionmentioning
confidence: 99%